CSUCI Wavelength 2008_05_09 (California State University Channel Islands)
Library event demonstrates resources for librarians, teachers May 9: The staff and faculty of the John Spoor Broome Library are hosting a special event to showcase the services available through the University's Library for local librarians and teachers. The open-house style event will be held from 3 to 5 p.m. on Friday, May 9. The event will be broken into brief information sessions and Library tours. Some sessions overlap and repeat so all attendees have the opportunity to attend most information sessions. Light refreshments will be served, and RSVPs are requested for planning purposes.